2018
DOI: 10.1186/s13287-018-1090-z
|View full text |Cite
|
Sign up to set email alerts
|

DMPE-PEG scaffold binding with TGF-β1 receptor enhances cardiomyogenic differentiation of adipose-derived stem cells

Abstract: BackgroundHeart failure has become a global health problem with increasing incidences worldwide. Traditional pharmacological treatments can delay but cannot reverse the underlying disease processes. The clinical application of myocardial tissue engineering represents a promising strategy because it features cell-based replacement therapies that replace partially or fully damaged cardiac tissues with in vitro-generated tissue equivalents. However, the effectiveness of this therapy is limited by poor viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Smooth muscle regeneration was mainly achieved by paracine factors or by direct differentiation into new smooth muscle tissue by injecting SCs. The interaction of cell surface receptors, ligands, and short-range-acting molecules between differentiated and undifferentiated cells significantly contributes to stem cell differentiation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smooth muscle regeneration was mainly achieved by paracine factors or by direct differentiation into new smooth muscle tissue by injecting SCs. The interaction of cell surface receptors, ligands, and short-range-acting molecules between differentiated and undifferentiated cells significantly contributes to stem cell differentiation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…used a polyethylene glycol‐conjugated phospholipid derivative (DMPE‐PEG) as a scaffold to bind recombinant TGF‐ β 1 receptor I to the surface of ADSCs. [ 183 ] Their results showed that the cardiomyogenic differentiation of ADSCs was significantly promoted by enhancing Smad2/3 phosphorylation. In addition, genetic modification of ADSCs has offered a potential route for inducing their differentiation into cardiomyocytes.…”
Section: Adscs In Regenerative Therapies: An Overview Of Recent Advan...mentioning
confidence: 99%
“…Synthetic biomaterials may be tailored to have high mechanical properties, with little batch-to-batch variability and immunogenicity, but they have limited functionality and resemblance to the natural cardiac ECM [179]. Synthetic biomaterials used for cardiac regeneration include polyethylene glycol [93,209], poly(lactic acid) [210,211], poly(lactic-co-glycolic acid) (PLGA) [212], poly (N-isopropylacrylamide) [213], and poly (glycerol sebacate) [211,214], as well as conductive materials such as polypyrrole [204,206], carbon nanotubes [215,216], gold [217,218], carbon nanofibers [219], and MXene [189] nanoparticles.…”
Section: Biomaterials In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Scaffolds, hydrogels High solubility, high manipulability, non-adhesive, non-toxic, highly stable [93,209] Poly(lactic acid) (PLA) Scaffolds, nanofibers Biocompatability, controllable degradation, ease of modification, non-toxic [210,211] Poly(lactic-coglycolic acid) (PLGA) Scaffolds, hydrogels Biocompatability, controllable biodegradability, ease of functionalization [212] Poly (Nisopropylacrylamide) (PIPAAm) Hydrogels Thermosensitivity, protein preservative, ease of conjugation to other substrates [213] Poly (glycerol sebacate) (PGS)…”
Section: Gelatinmentioning
confidence: 99%